1992
DOI: 10.4141/cjas92-038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of formaldehyde-treated barley or escape protein on nutrient digestibility, growth and carcass traits of feedlot lambs

Abstract: (32.6+2.4 kg) showed that DM intake and digestion of DM, organic matter, nitrogen and starch were similar among diets. DE was 3.8% lower (P < 0.05) for the formaldehyde-treated diet than the mean of the other two diets. ME was 5 .4% lower (P < 0.07) for the formaldehyde-treated barley than for the control diet. Digestion of NDF wasT .3% higher (P < 0.07) DM (%) oM (%) cP (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Lower ether extract apparent digestibility for cows fed formaldehyde-treated flaxseed compared with those fed Megalac or micronized soybeans has been reported by Petit et al (2002). Fluharty and Loerch (1989) found that N digestibility was reduced when corn was treated with 1 or 2% formaldehyde, but McAllister et al (1992) reported that treatment of barley with 0.11% formaldehyde did not affect N digestion or the amount of N retained. Fiems et al (1987) observed no difference in OM digestibility by calves fed diets with untreated or soybean meal treated with 0.2% formaldehyde, which was close to the 0.25 to 0.30% concentration applied to oilseeds in the present experiment.…”
Section: Resultsmentioning
confidence: 69%
“…Lower ether extract apparent digestibility for cows fed formaldehyde-treated flaxseed compared with those fed Megalac or micronized soybeans has been reported by Petit et al (2002). Fluharty and Loerch (1989) found that N digestibility was reduced when corn was treated with 1 or 2% formaldehyde, but McAllister et al (1992) reported that treatment of barley with 0.11% formaldehyde did not affect N digestion or the amount of N retained. Fiems et al (1987) observed no difference in OM digestibility by calves fed diets with untreated or soybean meal treated with 0.2% formaldehyde, which was close to the 0.25 to 0.30% concentration applied to oilseeds in the present experiment.…”
Section: Resultsmentioning
confidence: 69%
“…Formaldehyde treatment of feeds has also been reported to have bactericidal effects without apparent loss of palatability or growth reduction in poultry (Duncan and Adams 1972), and other food animals (Vanderwal 1979; Bugarski et al. 1990; McAllister et al. 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the absence of conclusive evidence of toxicity in humans who regularly work with formaldehyde, this substance has come to be regarded as hazardous (Arts et al, 2006). However, it does not appear to cause adverse effects or tissue residues in animals given feed or rations which have been treated (Duncan and Adams, 1972;Vanderwal, 1979;Buckley and Fisher, 1984;Bugarski et al, 1990;McAllister et al, 1992;Allen, 1993). In the EU, it is permitted as a feed processing aid, pending a review of the use of biocides and preservatives in foods and feedingstocks.…”
Section: Formaldehydementioning
confidence: 99%